Emerging Trends Around Resilience Leader: Systematic Review of Literature and Bibliometric Approach - Tri Annisa Irsan; Yunia Wardi; Ilham Thaib (Dinasti Publisher, 2024)
This research aims to conduct a systematic literature review and bibliometric approach to explore emerging trends around resilient leaders. This research method utilizes a systematic literature review (SLR) with a bibliometric approach using the keyword resilient leaders, totaling 46 manuscripts that will be reviewed further. The results can be explained by the fact that resilient leaders are confident in their ability to overcome challenges and lead effectively in complex situations. Resilient leaders are authentic leaders who emphasize honesty, integrity, and transparency as critical characteristics of strong leaders. The role of resilient leaders in digitalization highlights the ability of resilient leaders to lead organizations through digital transformation, ensuring that organizations remain resilient and adaptive in the ever-changing digital age.